Odpowiedź :
Odpowiedź:
1.
a) a+b=8+(-8)=8-8=0
b) a:b=(3 1/9) : (4 2/3)=28/9 : 14/3=28/9 * 3/14 = 2/3
c) a^3-b=(-0,1)^3-1=-0,001-1=1,001
2.
a)6x³yz=6*(1/2)³*(3/4)*(-2/3)=6*1/8*3/4*(-2/3)=-6/16=-3/8
b)pr²s=(-7/3)*(3/2)²*(-16/5)=(-7/3)*(9/4)*(-16/5)=84/5
c)2x⁴yz⁵=2*(-2)⁴*(-1/8)*(-1)⁵=2*16*(-1/8)*(-1)=4
1. Oblicz wartość liczbową wyrażenia.
a) a + b dla a = 8 b = -8
a + b = 8 + (-8) = 8 - 8 = 0
b) a : b dla a= 3 [tex]\frac{1}{9}[/tex] b= 4 [tex]\frac{2}{3}[/tex]
a : b = 3 [tex]\frac{1}{9}[/tex] : 4 [tex]\frac{2}{3}[/tex] = [tex]\frac{28}{9}[/tex] : [tex]\frac{14}{3}[/tex] = [tex]\frac{28}{9}[/tex] * [tex]\frac{3}{14}[/tex] = [tex]\frac{2}{9}[/tex] * 3 = [tex]\frac{2}{3}[/tex]
c) a³ - b dla a = -0,1 b = 1
(-0,1)³ - 1 = -0,001 - 1 - 0,999
2. Oblicz wartość liczbową jednomianu.
a) 6x³yz dla x = [tex]\frac{1}{2}[/tex] y = [tex]\frac{3}{4}[/tex] z = -[tex]\frac{2}{3}[/tex]
6x³yz = 6 * ([tex]\frac{1}{2}[/tex])³ * [tex]\frac{3}{4}[/tex] * (-[tex]\frac{2}{3}[/tex]) = 6 * [tex]\frac{1}{8}[/tex] * [tex]\frac{3}{4}[/tex] * (-[tex]\frac{2}{3}[/tex]) = -6 * [tex]\frac{1}{4}[/tex] * [tex]\frac{1}{4}[/tex] = -3 * [tex]\frac{1}{4}[/tex] * [tex]\frac{1}{2}[/tex] = -[tex]\frac{3}{8}[/tex]
B) pr²s dla p = (-2 [tex]\frac{1}{3}[/tex]) r = 1 [tex]\frac{1}{2}[/tex] s = (-3,2)
pr²s = -2 [tex]\frac{1}{3}[/tex] * ( 1 [tex]\frac{1}{2}[/tex] )² = -[tex]\frac{7}{3}[/tex] * ( [tex]\frac{3}{2}[/tex] )² = -[tex]\frac{7}{3}[/tex] * [tex]\frac{9}{4}[/tex] = -[tex]\frac{63}{4}[/tex] = -[tex]\frac{21}{4}[/tex]
C) 2x⁴yz⁵ dla x = -2 y = -[tex]\frac{1}{8}[/tex] z = -1
2x⁴yz⁵ = 2*(-2)⁴ * (-[tex]\frac{1}{8}[/tex]) * (-1)⁵ = 2*16*(-[tex]\frac{1}{8}[/tex]) * (-1) = 32 * (-[tex]\frac{1}{8}[/tex]) * (-1) = 4